Pengaruh Latihan Tangan Terhadap Tingkat Nyeri Pada Karyawan Home Industry Yang Mengalami Carpal Tunnel Syndrome - Rezagita Barthyana; Prita Adisty Handayani; Elis Hartati (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2021)
Pain is defined as a sensory experience and uncomfortable emotion concerning with the existence or potency of a broken tissue. Health problems at inconvenience working places may cause a certain disease. The disease deals with complaints on hands that may raise to CTS. This research aims to find out the influence of hand exercise toward pain level experienced by home industry workers with carpal tunnel syndrome in Karang Anyar Gunung village, Semarang. This is a pre-experimental designed research with One-Group Pretest-Posttest Design. The sample consisted of 30 respondents. They were taken by total sampling technique. This research used Numerical Rating Scale. The data was collected by having interview. The applied statistics test was wilcoxon test. The results showed that hand exercise was effective to reduce pain level of the employees suffering CTS with a p-value 0.001. By regularly applying this therapy on each task could decrease the pain scale of the home industry employees.